One‐step assembly and targeted integration of multigene constructs assisted by the I‐SceI meganuclease in Saccharomyces cerevisiae. Issue 8 (7th October 2013) - Kuijpers, Niels G.A.; Chroumpi, Soultana; Vos, Tim; Solis‐Escalante, Daniel; Bosman, Lizanne; Pronk, Jack T.; Daran, Jean‐Marc; Daran‐Lapujade, Pascale
Abstract In vivo assembly of overlapping fragments by homologous recombination in Saccharomyces cerevisiae is a powerful method to engineer large DNA constructs. Whereas most in vivo assembly methods reported to date result in circular vectors, stable integrated constructs are often preferred for metabolic engineering as they are required for large‐scale industrial application. The present study explores the potential of combining in vivo assembly of large, multigene expression constructs with their targeted chromosomal integration in S. cerevisiae. Combined assembly and targeted integration of a ten‐fragment 22‐kb construct to a single chromosomal locus was successfully achieved in a single transformation process, but with low efficiency (5% of the analyzed transformants contained the correctly assembled construct). The meganuclease I‐SceI was therefore used to introduce a double‐strand break at the targeted chromosomal locus, thus to facilitate integration of the assembled construct. I‐SceI‐assisted integration dramatically increased the efficiency of assembly and integration of the same construct to 95%. This study paves the way for the fast, efficient, and stable integration of large DNA constructs in S. cerevisiae chromosomes.